THE MODERATING ROLE OF SOCIAL IDENTITY ON THE RELATIONSHIP BETWEEN BEHAVIORALLY TARGETED ADS AND DONATION BEHAVIOR - Secioria, Rae (APPS Publications, 2019)
This article examines the role of behavioral targeting ads on the amount of donations on the condition of environmentally friendly products. Data from 240 college students were used to examine the main effect of behavioral targeting ads towards donating behavior, as well as the moderating effects of social identity and product positioning. The effect of social identity is based on the protection and improvement of self-concept. The threat to self-concept intuitively will be related to which identity is the strongest. Implication for managers is considered.